Perkembangan Moral Siswa Berbakat Intelektual - Hasyimi, Ali; Nurhayani (At-Tarbiyah: Journal of Islamic Religious Research and Education, 2024)
Genius children, or what in psychological terms are called gifted children, are children who have high intellectual talents. Gifted children show different characteristics from children their age, not only in cognitive development, but also in social and emotional development. Parents and teachers of gifted children often experience frustration and despair in dealing with gifted children's behavior. Ignorance of the behavior of gifted children, which is often considered to deviate from normal patterns, causes parents and teachers to think that the child has behavioral and mental disorders. A deep understanding of various aspects of the growth and development and personality of gifted children is very necessary to avoid misunderstandings about them. Gifted children often experience extraordinary growth and development that is different from other children. So far, educational attention for gifted children has focused more on intellectual aspects or academic problems, while attention to the intensity of personality factors is still very minimal. Many gifted children who should be able to develop their genius actually lose the opportunity to live and develop naturally.